Extremology: Behavioral and Quantitative Aspects - Vasyechko, O. O.; Chetverikov, O. F. (Statistics of Ukraine, 2020)
The contemporary era features systematic correlations between creating wealth and the emergence of new and even more intensive risks. Globalization processes, volatile geopolitical conjunctures, global climate change, technological progress, which provoke constant and inevitable change in the environment of our existence, aggravate the condition of uncertainty at each level of the social life, thus increasing the social and psychological tensions. The latter constitute another source of risks manifesting in the emergence of extreme environments or extreme situations, apart from conventional risks of human existence. It raises the need for rethinking of established paradigms in psychology and related or other sciences in which the notion “extreme” is in a way explored, and their revision, in order to form a new scientific synergy for methodological support of preparing the population to behavioral adaptation and situational behavior in extreme environments and situations. This determines high importance of extremology as a new applied and interdisciplinary research filed. Considering the social demand, analysis of scientific sources and own experiences of the authors, extremology can be defined as the system for the protection of populations and active counteractions in the conditions of emerging extreme environments and extreme situations. It is argued that to be effective nowadays, such system should be built on methods developed as part of other fields of knowledge, i. e. risicology and statistics, especially the component of extreme risk control and quantitative assessment. But the latter cannot exclude studies of the possibilities for enhancing cross-disciplinary synergy of extremology through involving other methods and practices.